3-D Network Pore Structures in Copper Foams by Electrodeposition and Hydrogen Bubble Templating Mechanism. Issue 8 (19th May 2015) - Zhang, Wenbin; Ding, Chuang; Wang, Aijun; Zeng, Yanwei
Abstract : Copper foams with various pore structures have been prepared using hydrogen bubbles as templates by electrodeposition method. By adjusting deposition time and incorporating different additives, the pore structures of copper deposit layers were effectively tuned as the results of controlled nucleation, growth, coalescence and detachment of hydrogen bubbles on the deposition interfaces. According to the analysis of experimental results, a tentative templating mechanism of hydrogen bubbles has been proposed, in which the well-grown hydrogen bubbles on the deposition interface are believed to contribute mostly to the formation of pore structures in the copper deposit layers, while the bubbles enlarged through interconnection and coalescence make no templating contributions due to their easy detachment from the interface. A larger average size of templating hydrogen bubbles at the upper layer than at the lower layer should arise from the quasi close-packing of growing hydrogen bubbles with their nucleation sites confined to the areas unoccupied by the pre-existing bubbles. In terms of this templating mechanism of hydrogen bubbles, the influences of relative concentrations of Cu 2+ and H + in the electrolyte solutions, deposition current density, chemical species and concentrations of additives on the evolution of pore-structures in the electrodeposited copper foams may be well explained and understood.